Associations of diabetes status and physical activity with cognitive impairment and hippocampal volume in older adults - Ryoki Mori; Hideyoshi Kaga; Yuki Someya; Hitoshi Naito; Hiroki Tabata; Eri Takagi; Toshiki Kogai; Shota Sakamoto; Saori Kakehi; Yuya Nishida; Ryuzo Kawamori; Hirotaka Watada; et al. (The Journal of Clinical Endocrinology & Metabolism, 2026)
Abstract Context Type 2 diabetes mellitus (DM) is a major risk factor for cognitive decline, whereas physical activity (PA) is associated with better cognitive health. We examined associations of DM status and PA level with cognitive impairment and hippocampal volume. Design and Setting This cross-sectional study included 1,615 community-dwelling older adults from the Bunkyo Health Study. PA was assessed using the International Physical Activity Questionnaire and classified as moderate-or-higher or low. Participants were categorized into 4 groups according to PA level and DM status. Cognitive impairment was defined as a Montreal Cognitive Assessment score ≤22, and hippocampal volume was measured by 0.3-T magnetic resonance imaging. Multivariable logistic regression and analysis of covariance were used to evaluate associations with cognitive impairment and hippocampal volume. Results Mean age was 73.1 ± 5.4 years, and 57.7% were women. Cognitive impairment prevalence was 15.6%, 19.7%, 20.4%, and 38.1% in the non-DM/high PA, non-DM/low PA, DM/high PA, and DM/low PA groups, respectively. Higher odds of cognitive impairment were observed only in the DM/low-PA group versus the non-DM/high-PA group (OR, 2.51; 95% CI, 1.40–4.49). Adjusted hippocampal volume was lower in the DM/low-PA group than in the non-DM groups. The DM × PA interaction did not reach statistical significance for either outcome. Conclusions Individuals with both DM and low PA had the highest prevalence of cognitive impairment and lower hippocampal volume. Neither interaction reached statistical significance; however, a moderate interaction for cognitive impairment could not be excluded, and the hippocampal findings should be interpreted cautiously.